WAWASAN HADIS TENTANG NIKAH MUTâAH (Suatu Kajian Mawdhuâiy) - Malik, Muhammad Anis (AL-MAIYYAH, 2015)
This paper examines the perspectives of marriage of mutah with a thematic approach. Elaboration of these issues resulted an understanding of mutâah is a marriage declared running for a certain time. Mutâah marriage is also known as the al-nikah al-munqatiâ (disconnected marriage) and the al-nikah al-muwaqqat (temporary marriage) which became one models of marriage in the early Islam. In the hadith context relating to mutâah marriage, indicates that there is a conflict between the hadith allowed mutah and hadith forbided mutah that all are in valid quality. The author offers two methods of settlement apparently contradictory hadith about marriage of mutah namely al-jamu methods and nasikh-mansukh methods that give different legal implications.